Exploring a new governance agenda: What are the questions that matter? - and Nixon, Nicola; Verhulst, Stefaan; Matin, Imran; Vermonte, Philips J. (2021)
The 100 Questions Initiative, pioneered by the GovLab, seeks to overcome the chasm between supply and demand. It begins not by searching for what data is available, but by asking important questions about the biggest challenges societies and countries face, and then seeking more targeted and relevant data solutions. In doing this, it narrows the gap between policy makers and constituents, providing opportunities for improved evidence-based policy and community engagement in developing countries. As part of this initiative, we seek to define the ten most important questions across several domains, including Migration, Gender, Employment, the Future of Work, and—now–Governance. On this occasion, we invited over 100 experts and practitioners in governance and data science –whom we call “bilinguals”– from various organizations, companies, and government agencies to identify what they see as the most pressing governance questions in their respective domains. Over 100 bilinguals were encouraged to prioritize potential impact, novelty, and feasibility in their questioning — moving toward a roadmap for data-driven action and collaboration that is both actionable and ambitious.